Acoustic and Psychological Effects of Omkar Chanting in Novice Indian Adults: A Quasi-experimental Study - Jayashree Pattanayak; Yamini Belur; Judu Ilavarasu (Journal of Clinical and Diagnostic Research)
Introduction: The physiological and psychological effects of Omkar chanting are gaining popularity. However, limited research has focused on the acoustic effects of Omkar chanting and how the produced sounds and vibrations influence both mental and vocal physiological states. Aim: This study explores the effects of 10 days of Omkar mantra chanting on voice quality and psychological well-being in Indian adults without prior regular chanting experience. Materials and Methods: A quasi-experimental study was conducted online in India involving 100 healthy adults (aged 20-45 years) over 10 days in three batches, from November 2023 to December 2023. Participants attended daily 30-minute Omkar chanting sessions. Four participants were excluded due to unclear audio recordings. Voice parameters and psychological well-being were assessed using PRAAT software, the World Health Organisation-Five Well-being Index (WHO-5), and the Subjective Vitality Scale, before and after the intervention. Data were analysed using paired sample t-tests to evaluate changes in voice parameters, vitality, and overall well-being. The level of significance was fixed at 0.05. Results: After 10 days of Omkar chanting, participants experienced significant improvements in their vocal quality, including reduced fundamental frequency (F0) for “A kara” (females: 223.06 to 216.58 Hz; males: 138.65 to 129.23 Hz) and “U kara” (females: 223.40 to 216.22 Hz; males: 138.40 to 131.13 Hz), as well as decreased jitter and shimmer values, reflecting increased vocal stability. There were significant increases in the mean WHO-5 scores (from 15.19 to 21.88) and mean vitality scores (from 23.76 to 35.34), (p-value <0.001), suggesting a positive impact on psychological well-being. These results indicate the beneficial effects of Omkar chanting on vocal health and psychological well-being in adults with no prior chanting experience. Conclusion: Omkar mantra chanting positively improves vocal stability, resonance, and mental health in adults aged 20-45 years. These findings suggest that incorporating mantra chanting into daily routines can be a simple yet effective tool for enhancing both vocal health and mental well-being, making it beneficial for those seeking natural practices for stress reduction and overall well-being.